Crime prevention and young people: Models and future direction for youth night patrols. Issue 4 (November 2016) - Cooper, Trudi; Scott, John; Barclay, Elaine; Sims, Margaret; Love, Terence
Abstract This article presents a typology of different approaches to social crime prevention adopted by Australian Indigenous youth night patrols. Research that informed this typology occurred in a specific context, but generic observations about youth crime prevention policy are transferable to community youth crime prevention in other settings. The typology identifies several key points of difference between various service delivery models, in particular, different perceptions of relationships between crime prevention; community safety; community development; community self-determination; child protection; and youth development and welfare. Discussion teases out how political discourse frames concepts such as community governance, self-determination, paternalism, and funding accountability. The discussion illustrates how politicised decision-making has meant that policy makers responded selectively to programme evaluations, in ways that did not always maximise benefit. The typology is intended to be useful to youth crime prevention practitioners, evaluators, and policy makers.